Systems Thinking Approach in Chemistry Education: How to Design Its Measurement Test - Asih Widi Wisudawati; Septy Nur Fadhilah (UIII Press, 2026)
The systems thinking approach in education requires analytical skills to examine complex problems and systems across multidisciplinary subjects. This approach focuses on how students analyze the components within systems and the interactions between subsystems that shape dynamic behavior. In education, systems thinking can engage multiple disciplines including science, social studies and religious studies. In chemistry education, however, this approach is recommended at the molecular level, reflecting the particulate nature of matter. While there are various systems thinking research reports in chemistry education, assessment tools to analyze the molecular basis of sustainability using this approach remain limited. This paper is aimed to design a chemistry test framework aligned with the systems thinking strands. Accordingly, this paper explains how to develop a construct map and design items, following the cyclical assessment development from Wilson’s four building blocks models. This resulted in a construct map assessment design that follows the four stages of systems thinking—identifying components, understanding their interactions within a dynamic system, calculating the involvement of these components based on the molecular basis of sustainability, and encouraging students’ mechanistic reasoning. According to the item design process, this paper merely reports the results of a pilot project and calculates content validity index using Aiken’s V. Here, we involved two experts, two teachers and 102 students who completed the test draft. The results show that the pattern of students’ answers follows the rubrics, and the test design is good. This study highlights the novel framework and its rubrics, but they need to be extended in the subsequent cycle of constructing measurement.